2015
DOI: 10.1159/000438601
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Eryptosis Following Exposure to Lopinavir

Abstract: Background/Aims: The protease inhibitor lopinavir, used for the treatment of HIV infections, triggers suicidal death or apoptosis of nucleated cells. Side effects of lopinavir include anemia, which could in theory result from stimulation of suicidal erythrocyte death or eryptosis, characterized by cell shrinkage and by phospholipid scrambling of the cell membrane leading to phosphatidylserine translocation to the erythrocyte surface. Stimulators of eryptosis include oxidative stress, increase of cytosolic Ca Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Example: Lopinavir treatment [22] induces oxidative stress and reduction of antioxidant glutathione as shown in Fig. 5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Example: Lopinavir treatment [22] induces oxidative stress and reduction of antioxidant glutathione as shown in Fig. 5.…”
Section: Methodsmentioning
confidence: 99%
“…Examples are provided by treatment of erythrocytes with the CDC25B phosphatase inhibitor NSC-95397 [35], the PLK1 kinase inhibitor BI-2536 [89], the protease inhibitor Lopinavir [22], the marine sponge-derived Fascaplycin [44], the selective histamine H1 receptor antagonist Terfenadine [58] and Fucoxanthin (a carotenoid from the chloroplasts of brown seaweeds) [25]. In parallel examples of substances interfering with eryptosis signalling, such as caspase inhibitor Z-VAD-FMK, p38 inhibitor SB203580, protein kinase C inhibitor staurosporine and casein kinase 1 CK1α inhibitor D4476 [9] are provided.…”
Section: Introductionmentioning
confidence: 99%
“…Another research group identified Lopinavir as a potent oxidative stress inducer, which causes ER stress, a common ART-induced side effect, in hepatocytes and in intestinal epithelial cells [12]. Instead, in erythrocytes from healthy volunteers Lopinavir treatment enhanced eryptosis, correlated again with oxidative stress [21]. Therefore, ART-treatment seems to increase oxidative stress in many different types of cellular models; unfortunately, the molecular mechanism underlying this effect is not yet fully elucidated and little is known about the relationship between oxidative stress and ART-treatment in CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Eryptosis is triggered by complement, hyperosmotic shock, energy depletion, oxidative stress, cellular K + loss, increase of temperature and a wide variety of xenobiotics [32, 43, 54, 64, 72-111]. …”
Section: Introductionmentioning
confidence: 99%